The value of extending life at its end: Health care allocation in the presence of learning spillovers - Beat Hintermann; Matthias Minke (University of Basel, Center of Business and Economics (WWZ), 2018)
We investigate the social value of medical interventions at the end of life that tend to have a high cost-benefit ratio. We model the optimal allocation of health resources across a continuum of diseases that dier by severity and treatment options, and extend it to allow for learning spillovers between treatments. We calibrate our model to admissions to intensive care units in Switzerland. Cancer treatments associated with learning spillovers that decrease the mortality for non-cancer patients by 1 percentage point justify a costbenefit ratio per additional life-year of 1.78.
Keywords: I10; 330; end of life; allocation of health resources; learning spillovers